APLIKASI TEKNOLOGI IRIGASI TETES PADA KEGIATAN BUDIDAYA TANAMAN VANILI DI RUMAH KACA DUSUN SINOGO, PAGERHARJO, SAMIGALUH, KULON PROGO, YOGYAKARTA - Suryanti, Sri; Mawandha, Hangger Gahara; Himawan, Achmad; Widyasaputra, Reza (Jurnal Abdi Insani, 2024)
Sinogo farmers, starting in November 2022 have cultivated Vanilla plants (Vanilla planifolia Andrews) in a greenhouse using planting medium in the form of mixture of soil, manure and cocofiber in a ratio of 1 : 1 : 1. The use of cocofiber causes the planting medium to dry out quickly. In 2023, Sinogo farmers had problem of limited water for watering because the water used comes from springs, which are very small during the dry season. The aim of the community service activity was to provide information about water-saving drip irrigation technology and to apply drip irrigation techniques to vanilla cultivation in greenhouses. Community service begins with survey activities to determine regional conditions and the level of farmers' understanding of drip irrigation technology. The next stage was education and practice of drip irrigation technology. Evaluation monitoring was carried out to determine the results of drip irrigation practices. The survey results showed that 87% of farmer group members did not know about drip irrigation techniques and they were very interested in implementing this technology. As many as 100% of respondents expressed interest in implementing drip irrigation technology on vanilla plants. After providing service to the Sinogo farmer community, they understood the drip irrigation technique, which was a water-saving irrigation technique. The results of the community service implementation showed that drip irrigation was running but was still limited because little water was stored due to low rainfall until December 2023. The conclusion was that most members of farmer community did not understand drip irrigation techniques. The success of drip irrigation techniques was influenced by the availability of water sources.